SIKAP BERHUBUNGAN DENGAN TINDAKAN IBU HAMIL DALAM MENGKONSUMSI TABLET ZAT BESI - Rahmawati, Naili (Ikatan Bidan Indonesia (IBI), 2022)
Background: Iron deficiency anemia is a decrease in the number of red blood cells caused by too little iron. According WHO (World Health Organization), in developing countries there are 40% of maternal deaths related to anemia during pregnancy. The frequency of pregnant women in Indonesia who experience anemia is still very high, namely 63.5% compared to only 6% in America. The number of pregnant women who experience anemia is due to a lack of knowledge of the mother, amounting to 45.6% of pregnant women do not know the consequences of anemia, do not regularly consume Fe tablets, and do not understand how to consume Fe tablets properly. Behavior is a predisposition to form an action. Pregnant women who have a positive behavior will be more obedient in consuming iron tablets, whereas pregnant women who have a negative behavior tend to act disobediently in consuming iron tablets during pregnancy. Action is an effort to manifest an behavior into a real action that requires supporting factors or enabling conditions Purpose: The objective of this study is to determine the correlation of behavior and actions of pregnant women in consuming iron tablet at the Midwives Independent Practice ‘I’. Methods: This research is a quantitative study with cross sectional approach. Data were collected using primary data. The research was conducted in August - September 2019. The population in this study were pregnant women at Praktik Mandiri Midwife I, as a sample. In this study, some of the pregnant women at the Midwife's Independent Practice I. Sampling was carried out using the accidental sumpling technique as many as 30 people. With the inclusion criteria, they can write, read, understand Indonesian and be in good health. Researchers used primary data, namely data obtained by interviewing a questionnaire instrument. Analysis of the data used in this study consisted of two stages of analysis as follows: univariate analysis. Univariate analysis and analysis of research data were carried out using the Spearman test. Results: The results showed that 100% of pregnant women had positif behavior, and 100% of pregnant women with good action in consuming iron tablets. Bivariate analysis using the Spearman test shows that there is a significant relationship between behavior and actions of pregnant women in consuming iron tablets. Conclusions: There is a significant correlation conclusion between knowledge and actions of pregnant women in consuming iron tablets . To increase the knowledge and actions of pregnant women in consuming iron tablets is required a counseling routinely and incresed distribution of iron tablet through cross program and cross sectoral activities.